2004
DOI: 10.1002/jctb.984
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of aqueous microenvironments in non‐ionic surfactant reverse micelles and their use for enzyme reactions in non‐aqueous media

Abstract: The polarity of water solubilized in the interior of non-ionic surfactant reverse micellar systems has been investigated using optical probes. Small amounts of water incorporated on the inside of various reverse micellar systems, polyoxyethylene sorbitan trioleate (Tween-85)/isopropyl alcohol/nhexane mixture and polyoxyethylene tert-octylphenyl ether (TX-100)/cyclohexane, were found to have low polarity compared with bulk water. The polarity of water in both Tween-85 and TX-100 reverse micellar systems corresp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…Because of their abnormal characteristics, micelles have been extensively exploited as models for understanding processes that are important for grasping the complex behavior encountered in biological assemblies [39,40]. It was observed that the observed rate constant values of the reaction increase with increasing [CTAB] (Table IV and Fig.…”
Section: Discussionmentioning
confidence: 94%
“…Because of their abnormal characteristics, micelles have been extensively exploited as models for understanding processes that are important for grasping the complex behavior encountered in biological assemblies [39,40]. It was observed that the observed rate constant values of the reaction increase with increasing [CTAB] (Table IV and Fig.…”
Section: Discussionmentioning
confidence: 94%
“…[12] These surfactants form a reversed micelle around the enzyme with the concomitant solubilization of small amounts of water, thereby providing a stable aqueous microenvironment. [28] The drawback of using this coating technique is the requirement of a more polar solvent such as THF. Water present in this solvent and in the reversed micelles adds up to give a relatively high water content in the reaction solution, increasing the risk of decomposition of 1 in the DYKAT reaction.…”
Section: Dynamic Kinetic Asymmetric Transformation (Dykat)mentioning
confidence: 99%
“…This implies that the cotton fabric shows a stronger dye adsorption performance in the TX-100 reverse micelle than in bulk water. The reason for this is that the water solubilised in the interior of the reverse micelle has a relatively low polarity than the bulk water [15,25], which leads to ionisation of the reactive dye molecule and the cotton fibre with difficulty in the micelle, thus reducing the repulsion force between the dye molecule and the fibre and improving the dye adsorption capacity. Another explanation is that the enhanced swelling of the cotton fibre observed in the TX-100 reverse micelle is possibly attributable to the penetration and wetting of the organic solvent and the TX-100.…”
Section: Dye Adsorption Isotherm Studiesmentioning
confidence: 99%
“…It was also reported that an ionic header group in the water-pool may act as a dyeing assistant and the adsorption of dye on fibre was greatly influenced by the charge on the surfactant molecule [12]. Moreover, the ionic head groups of the surfactant molecule used in reverse micelles had an adverse influence on the polarity of the water-pool and the uneven micro-environment produced might limit the application of reverse micelles [14,15]. Using nonionic surfactants may overcome the impact of the ionic head group of surfactant molecules on the micro-environment in the reverse micelle.…”
Section: Introductionmentioning
confidence: 99%